A legal study on the implementation of carpooling system in Klang Valley based on the Australian Road Rules 1999 / Nabila Shamsuddin, Nur Adila Mohd Sufian and Mohd Najib Mohd Razali - Shamsuddin, Nabila; Mohd Sufian, Nur Adila; Mohd Razali, Mohd Najib (2011)
In this project paper, the topic that had been discussed and research is concerning the implementation of a carpooling system in the Klang Valley based on the Australian carpooling system, as an alternative mode of transportation in reducing the traffic congestion as well as the level of air pollution in the urban areas, especially the Klang Valley. Several Malaysian statutes together with several Australian statutes had been referred to together with two international conventions regarding environmental protection for air pollution. References had also been made with a government bodies together with several experts in various fields such as environment, transportation and also insurance. This project paper will focus on the current problems faced by Malaysia due to the increasing number of private vehicles on the road, especially in the urban areas, and as in order to address these problems, we are proposing a carpooling system as one of the methods in reducing traffic problems and air pollution as similar carpooling system had been implemented successfully in Australia. Discussion also takes place concerning the amendments that have to be made to our local laws and legislations in accommodating such carpooling system. At the end of this project paper, we had outlined several issues and challenges that might and could happen or take place if the proposed carpooling system is implemented. However, several suggestions had also be discussed that can be used to address these issues and challenges and also to ensure the success of such system. It is hoped that this project paper would serve as a stepping stone for the actual implementation of a carpooling system in the Klang Valley.